Clinical Efficacy and Tolerability of Antihypertensive Therapy with Single Pill Combinations of Telmisartan in Patients with Arterial Hypertension in Clinical Practice According to the ON TIME Observational Study - F. T. Ageev; M. D. Smirnova (Рациональная фармакотерапия в кардиологии)
Aim. To assess the clinical outcomes and tolerability of antihypertensive therapy with single pill combinations (SPC) amlodipine + telmisartan and hydrochlorothiazide + telmisartan in clinical practice.Material and methods. Patients with hypertension of grade 1-3 (n=13647; 57.6% women; age 59.3±11.4 years) who received therapy with SPC amlodipine + telmisartan or hydrochlorothiazide + telmisartan were included in an observational multicenter study. Information on complaints, history, previous therapy, history of novel coronavirus infection (COVID-19) during the previous year was obtained. Also, measurement of height, body weight, waist circumference (WC) and hips (HC), office blood pressure (BP) three times with an interval of 4 weeks, completion of questionnaires of satisfaction with therapy using the Likert scale, and assessement of adherence to therapy according to the patient's opinion was performed.Results. A statistically significant decrease in systolic (SBP) and diastolic blood pressure (DBP) was found both in all patients and in the analysis of subgroups according to the grade of hypertension (p<0.001 between visits in all cases). The degree of BP reduction depended on baseline BP levels. The average decrease in SBP/DBP at the 3rd visit for the grade 1 hypertension was 24.5/14.6 mm Hg, for the grade 2 hypertension – 34.4/16.8 mmHg, for the grade 3 hypertension – 49.6/22.1 mmHg (p<0.001 between groups). Target levels of SBP (≤140 mmHg) and DBP (≤90 mmHg) were achieved in 95.3% and 98.1% of patients, respectively. Target levels of SBP (≤130 mmHg) and DBP (≤80 mmHg) were achieved in 74.9% and 78.2% of patients, respectively. WC decreased by 0.5%; HC – by 1.5%; body weight – by 0.42% (p<0.001 in all cases). Scores in patients with a history of COVID-19 did not differ from those in individuals without a history of COVID-19. There were no violations of the therapy regimen during the observation period in 94% of patients. Most doctors and patients were "satisfied" or "completely satisfied" with the clinical effect, convenience and tolerability of therapy. Adverse events occurred in 1.35% of patients.Conclusion. Therapy with SPC amlodipine + telmisartan or hydrochlorothiazide + telmisartan in clinical practice had a high antihypertensive efficacy and had an optimal safety profile. The efficacy of therapy did not depend on the initial grade of hypertension, as well as the past infection with COVID19. The results of the ON TIME study confirm the feasibility of using the SPC amlodipine + telmisartan and hydrochlorothiazide + telmisartan for a wide range of hypertensive patients.